Graphene nanoribbon FET technology‐based OTA for optimizing fast and energy‐efficient electronics for IoT application: Next‐generation circuit design - Faraz Hashmi; M Nizamuddin; Mohammad Aleem Farshori; Syed Umar Amin; Zafar Iqbal Khan (Micro & Nano Letters)
Abstract The Internet of Things (IoT) and portable electronic devices are pivotal in enhancing living standards, with battery efficiency and compact design being critical for these devices. Analogue sensors, integral to advanced artificial intelligence, often necessitate complex real‐time processing and actuation. This study examines the performance of one‐dimensional armchair graphene nanoribbons in graphene nanoribbon field‐effect transistors (GNRFETs). It compares graphene nanoribbon‐based triple cascode operational transconductance amplifiers (GNRFET‐TCOTAs) with conventional CMOS‐based TCOTA. The results reveal substantial enhancements in the GNRFET‐based TCOTAs: the pure GNR‐TCOTA variant shows a remarkable 33.8% increase in DC gain and significant improvements in transconductance, slew rate, and gain‐bandwidth, with enhancements of 8.48, 5.85, and 8.56 times, respectively. Furthermore, the pure GNRFET TCOTA exhibits higher speed, lower energy‐delay product, and settling time compared to Si‐CMOS‐based TCOTA. The study also investigates the impact of critical design parameters on circuit performance. Overall, the research highlights the potential of GNRFETs to optimize TCOTA circuits, offering a path towards more efficient and compact electronic devices, thereby advancing the state of nanoelectronics and supporting the growth of high‐performance IoT systems.